Respostas
respondido por:
28
Oi,
Resolução
2x + 4y = 3 . (2)
4x -8y=2
4x + 8y = 6
4x - 8y = 2
8x = 8
x = 1
2x + 4y = 3
2 (1) + 4y = 3
2 + 4y = 3
4y = 3 - 2
4y = 1
y = 1/4
S = {( 1 ; 1/4 )}
Espero ter ajudado e bons estudos !
Resolução
2x + 4y = 3 . (2)
4x -8y=2
4x + 8y = 6
4x - 8y = 2
8x = 8
x = 1
2x + 4y = 3
2 (1) + 4y = 3
2 + 4y = 3
4y = 3 - 2
4y = 1
y = 1/4
S = {( 1 ; 1/4 )}
Espero ter ajudado e bons estudos !
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás